1987
DOI: 10.1002/1097-0142(19870115)59:2<208::aid-cncr2820590205>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in angioimmunoblastic lymphadenopathy

Abstract: In order to identify prognostic factors in angioimmunoblastic lymphadenopathy (AIL), 30 directly diagnosed patients were prospectively followed for more than 42 months. Age and sex distribution, clinical and laboratory findings and evolution were not different from previously reported series. Median duration of survival was 24 months. Parameters associated with a longer survival in our series were localized adenopathies (P = 0.01) and the achievement of a remission (P < 0.0001). Features associated with a shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…7,8 Roquin san/ϩ mice displayed a slight but significant (P Ͻ .05) increase in spleen weight compared with control Roquin ϩ/ϩ mice ( Figure larger than lymph nodes from Roquin ϩ/ϩ control mice (data not shown).…”
Section: Roquin Mutations Cause Aitl-like Tumors In Mice 813mentioning
confidence: 87%
See 2 more Smart Citations
“…7,8 Roquin san/ϩ mice displayed a slight but significant (P Ͻ .05) increase in spleen weight compared with control Roquin ϩ/ϩ mice ( Figure larger than lymph nodes from Roquin ϩ/ϩ control mice (data not shown).…”
Section: Roquin Mutations Cause Aitl-like Tumors In Mice 813mentioning
confidence: 87%
“…Sinusoidal dilatation was also evident, as well as vessels filled with T cells. A prominent feature present in most AITL cases, but absent in the tumors of Roquin san/ϩ mice, is prominent expansion of the FDC network, 3,7,8,27 as determined by an absence of CD21 ϩ dendritic cells in lymph node sections (data not shown). Together, this histologic appearance is highly reminiscent of AITL.…”
Section: Histopathology Of Roquin San/؉ Lymph Nodes Is Reminiscent Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…23, 24 The Kiel Lymphoma Study Group analyzed the prognostic impact of clinical observations and laboratory findings at presentation and found that survival was significantly related to age (P ϭ .032), stage (P ϭ .037), systemic symptoms (P ϭ .007), skin rash/pruritus (P ϭ .038), edema (P ϭ .030), ascites (P ϭ .013), high LDH (P ϭ .007), and decreased hemoglobin (P ϭ .020). 9 Archimbaud et al 24 identified prognostic factors associated with shorter survival, including rash (P Ͻ .001), lymph node eosinophilia (P ϭ .03), elevated LDH (P ϭ .03), and drug exposure in relation to the onset of the disease (P ϭ .02); parameters associated with longer survival were localized lymphadenopathy (P ϭ .01) and achievement of remission (P Ͻ .001).…”
Section: Discussionmentioning
confidence: 99%
“…9 Archimbaud et al 24 identified prognostic factors associated with shorter survival, including rash (P Ͻ .001), lymph node eosinophilia (P ϭ .03), elevated LDH (P ϭ .03), and drug exposure in relation to the onset of the disease (P ϭ .02); parameters associated with longer survival were localized lymphadenopathy (P ϭ .01) and achievement of remission (P Ͻ .001). In our study, an alternative prognostic model for AITL was constructed using the five clinical prognostic factors: age Ͼ 60 years, PS Ն 2, ENSs Ͼ one, B symptoms, and platelet count Ͻ 150 ϫ 10 9 /L.…”
Section: Discussionmentioning
confidence: 99%